Fish culling reduces tapeworm burden in Arctic charr by increasing parasite mortality rather than by reducing density‐dependent transmission. Issue 6 (15th March 2019) - Henriksen, Eirik H.; Frainer, André; Knudsen, Rune; Kristoffersen, Roar; Kuris, Armand M.; Lafferty, Kevin D.; Amundsen, Per‐Arne
Abstract: Two common Dibothriocephalus (formerly Diphyllobothrium ) tapeworm species were significantly reduced by experimental culling of their fish host Arctic charr ( Salvelinus alpinus ) in a subarctic lake. Between 1984 and 1991, funnel traps were used to cull 35 metric tons of Arctic charr, reducing charr density by 80%. As charr densities decreased, tapeworm prevalence and then intensity also declined over the following three decades, with D. dendriticus (formerly dendriticum ) responding faster than D. ditremus (formerly ditremum ). The two main hypotheses for how culling a host can decrease parasitism are reductions in parasite transmission due to reduced host density and reductions in parasite survival through increases in host mortality rates. We found little evidence that charr density was the main driver for reduced parasite transmission. Instead, decreased survivorship in charr, initially, through fishing‐induced changes in charr age structure, and later through increased predation rates by brown trout, led to increased parasite mortality. Although brown trout, which increased significantly after fish culling, are also hosts, they are often too big for the final host birds to eat, thus becoming parasite sinks. Synthesis and applications . Fish populations with heavy parasite burdens constitute a management problem. Our results show how fish culling can indirectly reduce transmitted parasites through increased parasite mortality. Managing overcrowded fish populations by culling can produce two desirable outcomes: an increase in fish growth rates and reduced parasite burdens. Abstract : Fish populations with heavy parasite burdens constitute a management problem. Our results show how fish culling can indirectly reduce transmitted parasites through increased parasite mortality. Managing overcrowded fish populations by culling can produce two desirable outcomes: an increase in fish growth rates and reduced parasite burdens.